Arabic Morphology: Derivational Patterns and Their Application in Arabic Language Teaching - Maesaroh, Windah; Cahyani, Aceng; Al-Madani, Ibnu Khanif; Susiawati, Iis (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
The morphological system in Arabic, with a focus on word derivation patterns and their application in Arabic language learning for non-Arabic speakers. Arabic has a distinctive word formation system, based on root words and phonological patterns, which allows for the formation of various words with different meanings and syntactic functions. This study uses a qualitative-descriptive method through a literature review approach to relevant linguistic and pedagogical sources. The results of the study show that understanding word patterns such as agent nouns, object nouns, verbs, and abstract nouns can systematically strengthen students' vocabulary and grammar skills. In learning practice, effective strategies include derivation exercises, word analysis in authentic texts, the use of visual media, and the integration of word patterns in teaching modules. This approach not only improves students' linguistic abilities but also encourages them to understand the structure and meaning of words more deeply. In addition, morphology-based learning helps students recognize relationships between words, expand their vocabulary productively, and understand the syntactic context in Arabic sentences. This study concludes that Arabic language teaching that integrates morphological analysis can be an important foundation in the development of a communicative, analytical, and contextual curriculum that is relevant to modern learning needs.